PENERAPAN TAX PLANNING TERHADAP PPh SEBAGAI UPAYA EFISENSI PEMBAYARAN PAJAK (Studi Kasus Pada Perusahaan Jasa Angkutan Di Malang) - Wahyuni, Nanik (IQTISHODUNA, 2009)
To the effect of observational it is subject to be to insofar know which income tax planning effectiveness that can be done by firm and to reach efficiency in paying taxes charges that shall pay firm. Base observational result and taxation problem study in particular about tax planning on, therefore writer can glean from that firm has applied effective so corporate tax planning can't economize taxes charges payment it. To economize taxes, expedition company ought to applies tax planning, which is with shift cost that don't be admitted fiskus as accrued expenses fiskus as deducted as productions. In shifts cost, firm shall regard impact of that cost shift. Meanwhile to avoid of corporate maximum tax rate gets to broadcast production as production of some taxpayer, which is with make proprietary branch office as new firm that includes in group firm, then broadcasts proprietary production corporate to that new firm. With that implement, firm can economize taxes who shall be paid to state, and that thrift gets to be utilized to do marketing region extension and for things what do get to increase quality and firm amount.